(untitled) - Murphy, Josette (Wageningen, 1982)
The book is presented in two parts. Part 1, General principles, describes, step by step, how to organize a monitoring and evaluation unit. Part 2, Methologies, is a detailed elaboration of the activiteis described in part 1. It also discusses the problems likely to occur, so that the person called upon to organize a monitoring and evaluation unit will be forewarned
Keywords: Agriculture; Economic aspects